MBCL-21. GERMLINE ELONGATOR MUTATIONS IN SONIC HEDGEHOG MEDULLOBLASTOMA. (4th December 2020) - Robinson, Giles W; Waszak, Sebastian M; Gudenas, Brian L; Smith, Kyle S; Forget, Antoine; Kojic, Marija; Jesus, Garcia-Lopez; Hadley, Jennifer; Hamilton, Kayla V; Indersie, Emilie; Buchhalter, Ivo; Jager, Natalie; et al.
Abstract: BACKGROUND: Our previous analysis of established cancer predisposition genes in medulloblastoma (MB) identified pathogenic germline variants in 5% of all patients. Here, we extended our analysis to include all protein-coding genes. METHODS: Case-control analysis performed on 795 MB patients against >118, 000 cancer-free children and adults was performed to identify an association between rare germline variants and MB. RESULTS: Germline loss-of-function variants of Elongator Complex Protein 1 ( ELP1 ; 9q31.3) were strongly associated with SHH subgroup (MBSHH ). ELP1 -associated-MBs accounted for 15% (29/202) of pediatric MBSHH cases and were restricted to the SHHα subtype. ELP1 -associated-MBs demonstrated biallelic inactivation of ELP1 due to somatic chromosome 9q loss and most tumors exhibited co-occurring somatic PTCH1 (9q22.32) alterations. Inheritance was verified by parent-offspring sequencing (n=3) and pedigree analysis identified two families with a history of pediatric MB. ELP1 -associated-MBSHH were characterized by desmoplastic/nodular histology (76%; 13/17) and demonstrated a favorable clinical outcome when compared to TP53 -associated-MBSHH (5-yr OS 92% vs 20%; p-value=1.3e-6) despite both belonging to the SHHα subtype. ELP1 is a subunit of the Elongator complex, that promotes efficient translational elongation through tRNA modifications at the wobble (U34 ) position. Biochemical, transcriptional, and proteomic analyses revealed ELP1 -associated-MBs exhibit destabilization of the core Elongator complex, loss of tRNA wobble modifications, codon-dependent translational reprogramming, and induction of the unfolded protein response. CONCLUSIONS: We identified ELP1 as the most common MB predisposition gene, increasing the total genetic predisposition for pediatric MBSHH to 40%. These results mark MBSHH as an overwhelmingly genetically-predisposed disease and implicate disruption of protein homeostasis in MBSHH development.